Functional Electrical Stimulation Therapy for Recovery of Reaching and Grasping in Severe Chronic Pediatric Stroke Patients. (April 2014) - Kapadia, Naaz M.; Nagai, Mary K.; Zivanovic, Vera; Bernstein, Janet; Woodhouse, Janet; Rumney, Peter; Popovic, Milos R.
Stroke affects 2.7 children per 100, 000 annually, leaving many of them with lifelong residual impairments despite intensive rehabilitation. In the present study the authors evaluated the effectiveness of 48 hours of transcutaneous functional electrical stimulation therapy for retraining voluntary reaching and grasping in 4 severe chronic pediatric stroke participants. Participants were assessed using the Rehabilitation Engineering Laboratory Hand Function Test, Quality of Upper Extremity Skills Test, Pediatric Evaluation of Disability Inventory, and Assisting Hand Assessment. All participants improved on all measures. The average change scores on selected Rehabilitation Engineering Laboratory Hand Function Test components were 14.5 for object manipulation ( P = .042), 0.78 Nm for instrumented cylinder ( P = .068), and 14 for wooden blocks ( P = .068) and on the grasp component of Quality of Upper Extremity Skills Test was 25.93 ( P = .068). These results provide preliminary evidence that functional electrical stimulation therapy has the potential to improve upper limb function in severe chronic pediatric stroke patients.